Private Tutoring and Academic Achievement in a Selective Education System - Maria Zumbuehl; Stefanie Hof; Stefan C. Wolter (Institute of Labor Economics (IZA), 2022)
Decisions about admission to selective schools usually rely on performance measures. To reach a required achievement threshold students may make use of additional resources, such as private tutoring. We investigate how the use of private tutoring relates to the transition probability to an academically demanding post compulsory school and the probability to successfully pass through this school, controlling for the students competencies after tutoring, but before the transition. Using PISA and linked register data from Switzerland, we find that students who had private tutoring before the transition are more likely to fail in the selective school than students who had the same level of competencies without tutoring.
Keywords: D82; I21; I24; 330; private tutoring; educational achievment; PISA; Switzerland